SANKSI PELAKU PENGGELAPAN PAJAK DALAM PERSPEKTIF HUKUM PIDANA ISLAM (ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR: 1030K/PID.SUS/2016 - Ma'ruf, Fauzan; Marsaid, Marsaid (Universitas Islam Negeri Raden Fatah Palembang, 2020)
In the Decision of the Supreme Court Number: 1030K / PID.SUS / 2016, it is known that the decision of the District Court Judge is not in accordance with the Law because it sub-subsidizes the fine, while in the High Court Judge Decision has also wrongly applied the sentence because it only gave a fine sentence in the year 2008 whereas 2009 was not awarded. Therefore, it is interesting to see the verdict that will be given by the Supreme Court Judge. There are two things that are raised to be the focus of the research, namely the basis for the consideration of Supreme Court judges and the analysis of Islamic criminal law on the sanctions for tax evasion perpetrators in Decision Number: 1030K / PID.SUS / 2016. The method used in this research is Normative Law Research, which aims to obtain theoretical matters through library research (Library Research). The type of data used is qualitative, while the source of the data taken in this study is secondary data which is obtained from data that has been processed and obtained from library materials. Then this discussion is described in a deductive way of thinking, namely from general to specific questions so that the presentation of the research results can be understood easily. The basis for consideration of Supreme Court judges in Decision Number: 1030 K / PID.SUS / 2016 is in accordance with juridical, philosophical, and sociological aspects. As for Islamic law, the sanctions for tax evasion perpetrators in the decision Number: 1030 K / PID.SUS / 2016 are categorized into Jarimah ta'zir. Keywords: Criminal Sanctions, Tax Embezzlement, Ta'zir